Decreased Hospital Visits and Increased Mortality Rate in Emergency Department during the COVID-19 Pandemic: Evidence from Albania - Bucaj, Jorgjia; Mechili, Enkeleint A.; Galanis , Petros; Mersini , Bruna; Nika, Sonila; Hoxhaj , Inis; Likaj , Stefano; Patelarou , Athina E.; Patelarou , Evridiki (Acta medica Lituanica, 2022)
Objective: To investigate the hospital visits and mortality rate during the COVID-19 in emergency department of Vlora regional hospital in Albania and to compare with the three previous years (2017–2019). Methods: Secondary data of patients that visited emergency department of Vlora Regional hospital Albania (largest hospital in the south of the country), since January 1, 2017 till December 31, 2020. This is a retrospective study. We used the hard copy of the patients’ health register records. The data extraction was conducted during March 2021 till June 2021. Eligible were all patients admitted and recorded in the registry of the emergency department. The causes of admission were categorized in 14 different disease categories. All registered patients admitted to the Vlora regional hospital were included in the study. Results: Study population included 44,917 patients during 2017–2020. Mean age of patients was 51.5 years, while 53.6% were females. The highest number of patients was in 2017 (n=12,407) and the lowest in 2020 (n=9,266). Increase of patients presented with cardiovascular, psychiatric and renal/urinary tract was observed in 2020 in comparison to 2019. Patients decreased over time with an average annual percent decrease of 7% (p-value=0.22). Joinpoint analysis revealed that mortality rate increased over time with an average annual percent increase of 34.3% (95% confidence interval=42.7% to 214.8%, p-value=0.27). Conclusions: The number of patients visiting emergency department decreased while mortality rate increased. Educating and raising awareness of patient to seek medical assistance should be a key objective of health policy makers and health personnel.